2019
DOI: 10.21608/jacb.2019.60235
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with Single, Dual or Consortia of Rhizobium leguminosarum bv. trifolli , Pseudomonas stutzeri and Anabaena sp. and their effect on Yield Components of Rice Plant

Abstract: A set of six rice field inoculation trials was selected at two governorates in Egypt located at the Nile delta. These study was conducted to investigate the response yield components of three Egyptian rice varieties (Sakha 101, Giza 177 and Giza 178) to inoculation with three bacterial strains (Rhizobium leguminosarum bv. trifolli (RH) strain E11, Anabaena sp. strain ERC102 and Pseudomonas stutzeri strain ERP1) and their combination in the presence of three levels of nitrogen (48,96 and 144 kg N/ha.). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…2 and 3 ), barley, and cowpea growth (Table 5 ). This result agreed with previous studies, where the positive effects of these strains on several plants were attributed to their nitrogen-fixing abilities [ 44 46 ]. Ammonia production is not an uncommon trait in endophytic bacteria from root nodules and is related to nitrogen fixation [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…2 and 3 ), barley, and cowpea growth (Table 5 ). This result agreed with previous studies, where the positive effects of these strains on several plants were attributed to their nitrogen-fixing abilities [ 44 46 ]. Ammonia production is not an uncommon trait in endophytic bacteria from root nodules and is related to nitrogen fixation [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Application of inoculation with two cyanobacterial strains, their extracts and compost tea under three doses of inorganic nitrogen increased Nitrogen-fixing cyanobacteria and bacterial rhizosphere soil content, plant growth parameters and yield of wheat plant. And from root biovolume and shoot length were taken as index for the plant growth promotion activity of the tested strains (Hauka et al, 2012). Therefore, it would be recommended to apply these strains of cyanobacteria in bioorganic farming (Zaki et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacterial extracts are fertilisers can be prepared a by different materials such as water (Shariatmadari et al, 2013) and chemicals such as methanol (Chookalaii, 2020) used to have final cyanobacterial extract. Hauka et al (2012) reported that the plant growth promotion provided by inoculation with mixed better than alone or when the strains were mixed in a consortia inoculum. Also, Rana et al (2012) found that Anabaena sp.…”
Section: Introductionmentioning
confidence: 99%